2020
DOI: 10.1021/acsenergylett.0c02349
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Activated Electrochemical Ammonia Synthesis from Nitrogen and Water

Abstract: Ammonia is an important precursor of fertilizers, as well as a potential carbon-free energy carrier. Nowadays, ammonia is synthesized via the Haber-Bosch process which is capital-and energyintensive process with an immense CO 2 footprint. Thus, alternative processes for the sustainable and decentralized ammonia production from N2 and H2O using renewable electricity are required.The key challenges for the realization of such processes are the efficient activation of the N2 bond and selectivity towards NH3. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…Additionally, the use of fertilizers, especially those with low quality and control, to increase the crop yield often results in the heavy metal soil contamination [5]. On the contrary, with the use of PAW or plasma activated ammonia solutions, such contamination can be avoided, as these solutions may serve as an effective source of nitrogen with nitrates (NO 3 − ) and ammonium ions (NH 4 + ) being the most important compounds for plant growth and development [6]. Further, hydrogen peroxide (H 2 O 2 ) can serve to sterilize seeds and can also enhance seed priming.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of fertilizers, especially those with low quality and control, to increase the crop yield often results in the heavy metal soil contamination [5]. On the contrary, with the use of PAW or plasma activated ammonia solutions, such contamination can be avoided, as these solutions may serve as an effective source of nitrogen with nitrates (NO 3 − ) and ammonium ions (NH 4 + ) being the most important compounds for plant growth and development [6]. Further, hydrogen peroxide (H 2 O 2 ) can serve to sterilize seeds and can also enhance seed priming.…”
Section: Introductionmentioning
confidence: 99%
“… 87 Kumari et al reported plasma-aided N 2 electroreduction that enabled a 47% increase in ammonia production in comparison with conventional electrochemical reduction. 88 Sharma reported the integration of plasma into a proton-conducting solid oxide electrolyzer and achieved a benchmark-high ammonia production rate of 964.8 μmol h –1 cm –2 with an NH 3 FE of 10%, 89 corresponding to an ammonia partial current density of 77.57 mA cm –2 . Recently, Qiao and collaborators coupled a low-temperature plasma oxidation with electrochemical reduction, demonstrating N 2 conversion to ammonia via nitrate as an intermediate.…”
Section: Electrochemical N 2 Cyclementioning
confidence: 99%
“…These nitrogen derivatives are the mobile and soluble forms of nitrogen in soil, which makes them more suitable for plant uptake [19,20]. NTAPP methods could prove to be superior to existing fertilizer technology for the following reasons: (i) They operate under atmospheric conditions using sustainable energy [21,22]. (ii) In contrast to the H-B process, they do not emit any greenhouse gases [23,24].…”
Section: Introductionmentioning
confidence: 99%